Parasocial Interactions and Relationships in Early Adolescence - Gleason, Tracy R.; Theran, Sally A.; Newberg, Emily M. (Frontiers in Psychology, 2017)
Parasocial interactions and relationships, one-sided connections imagined with celebrities and media figures, are common in adolescence and might play a role in adolescent identity formation and autonomy development. We asked 151 early adolescents (Mage = 14.8 years) to identify a famous individual of whom they are fond; we examined the type of celebrities chosen and why they admired them, and the relationships imagined with these figures across the entire sample and by gender. Adolescents emphasized highly salient media figures, such as actors, for parasocial attention. While different categories of celebrities were appreciated equally for their talent and personality, actors/singers were endorsed for their attractiveness more so than other celebrity types. Most adolescents (61.1%) thought of their favorite media figures as relationship partners, and those who did reported more parasocial involvement and emotional intensity than those who did not. Gender differences emerged in that boys chose more athletes than girls and were more likely to imagine celebrities as authority figures or mentors than friends. Celebrities afforded friendship for girls, who overwhelmingly focused on actresses. Hierarchical parasocial relationships may be linked to processes of identity formation as adolescents, particularly boys, imagine media figures as role models. In contrast, egalitarian parasocial relationships might be associated with autonomy development via an imagined affiliation with an attractive and admirable media figure.